2022
DOI: 10.3390/electronics11193223
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Enabling IoT in Healthcare: Motivations, Challenges, and Recommendations

Abstract: improving mobility, gathering medical data, and decreasing hospital and patient costs. IoT in healthcare is still one of the hot and trendy topics that needs in-depth investigation. No recent review has been conducted to elucidate the extent of research in the area, features of published papers, motives, and challenges in enabling IoT in healthcare systems. This study presents a comprehensive systematic review of the screened articles published between 2015 and 2022 pertaining to enabling IoT in healthcare ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 110 publications
(337 reference statements)
0
4
0
Order By: Relevance
“…The writers gave the SLR title their entire attention, but they failed to adequately handle QoS, one of the toughest problems in healthcare. The article's [37] major goal was to make clear the standards and factors to be considered when integrating IoT into healthcare systems. In addition to a comprehensive SLR, questionnaires and surveys were also conducted to investigate several IoT-based healthcare solutions.…”
Section: Systematic Literature Reviews/surveys/reviewsmentioning
confidence: 99%
“…The writers gave the SLR title their entire attention, but they failed to adequately handle QoS, one of the toughest problems in healthcare. The article's [37] major goal was to make clear the standards and factors to be considered when integrating IoT into healthcare systems. In addition to a comprehensive SLR, questionnaires and surveys were also conducted to investigate several IoT-based healthcare solutions.…”
Section: Systematic Literature Reviews/surveys/reviewsmentioning
confidence: 99%
“…We adapted the questionnaire's items from many research papers [3,5,6,26]. The variables of our research are the following: Assessment of the level of digitalization of the medical field-DEC (4 items); The usability and availability of new technology-DTEC (4 items); Evaluation of the level of awareness by young people with a background in the medical field of their entrepreneurial potential-EP (4 items); and the motivation of young people with a background in the medical field to become entrepreneurs-MME (5 items).…”
Section: The Structure Of the Questionnairementioning
confidence: 99%
“…One of the main motivations of young people with a background in the medical field to develop their entrepreneurial competencies in connection with promoting new technology consists of placing value on the unexploited potential of digital tools to reduce inequalities among patients and to increase patients' healthcare access across all categories. Mohamad Jawad et al [3] analyzed 106 papers and observed that researchers have paid huge attention to the impact of new technology on patients' and medical employees' lives. Therefore, to increase the potential of the new technology, it must be smartly and efficiently used.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 provides an overview of the security and privacy technologies used in various HISs [3]. technology, such as blockchain and the Internet of Things (IoT) [5,6]. So far, most of these studies have not comprehensively explained and reviewed the various technologies for ensuring the privacy and security of medical data.…”
Section: Introductionmentioning
confidence: 99%